Predicting high-quality ecologically suitable areas of Astragalus mongholicus Bunge based on secondary metabolites content using Biomod2 model - Jingyi Zhou; Xiaoting Zhang; Tongtong Huo; Huizhong Xu; Fanyun Meng; Ning Xu; Cheng Peng (Scientific Reports)
Abstract Habitat requirements and species’ ecological suitability are essential conditions for species conservation and management. Under the influence of different environmental variables, assessing the habitat quality of medicinal plants is an important issue to ensure the quality of medicinal plants and protect biodiversity. This study explores the impact of environmental variables on the distribution of Astragalus mongholicus Bunge (A. bunge) and the content of effective secondary metabolites (SMs). Combining the Biomod2 model, we constructed a Comprehensive Geospatial Quality Model (CGQM) for A. bunge under current environmental conditions, obtaining a high-quality comprehensive suitable area for A. bunge. The results indicate that the area of the comprehensive high-suitable zone is 4.53 × 105 km2, accounting for 21.91% of the suitable area for A. bunge. It is mainly distributed in the eastern and western parts of Shanxi, the northwest of Shaanxi, the southern part of Ningxia, the southeast of Gansu, the northern part of Hebei, the eastern part of Beijing, the northeastern part of Jilin, the central and southern parts of Inner Mongolia, and a very small part of Xinjiang.